Current Status of Malignant Neuropathic Pain in Chinese Patients with Cancer: Report of a Hospital‐based Investigation of Prevalence, Etiology, Assessment, and Treatment. Issue 1 (15th March 2016) - Lu, Fan; Song, Li; Xie, Tian; Tian, Jie; Fan, Yuchao; Liu, Hui
Abstract: Objectives: This study investigated the prevalence, etiology, assessment, treatment of pain in patients with cancer as well as their quality of life (QOL). Methods: Patients at the West China Hospital Cancer Center were invited to complete a questionnaire under the guidance of pain specialists. The questionnaire included general information, cancer pain status, its assessment, use of analgesics, and the effects of pain on QOL. Results: In total, 1, 050 patients were enrolled in the study. Of these, valid data were collected from 919 patients, among whom 454 (49.4%) suffered from pain, including 333 (36.2%) patients who had neuropathic pain symptoms. On average, the visual analog scale (VAS) score of patients with cancer pain was 3.30 ± 1.68. Significant differences in the VAS score and pain frequency between patients with nociceptive and neuropathic pain were observed (both P < 0.05). Dull pain ranked first (64, 52.9%) among the patients with nociceptive pain, whereas pins and needles pain (97, 64.7%) was the most common type of pain in patients with neuropathic pain. There was a significant difference in QOL between the nociceptive and neuropathic pain groups ( P < 0.05). Only 183 of 454 patients with cancer pain used analgesics. Compared with the patients with pain not using any analgesics, those receiving analgesics had a significantly lower average pain relief rate ( P = 0.027). Adjuvant analgesics were inadequately used (9.3%) in patients with neuropathic cancer pain. Conclusion: This study revealed the prevalence of neuropathic cancer pain in Chinese patients with cancer. Malignant neuropathic pain significantly impaired the patients' QOL. Insufficient assessment and inadequate analgesia still exist. These require more awareness and attention from both doctors and patients.